2022
DOI: 10.1186/s43055-022-00694-3
|View full text |Cite
|
Sign up to set email alerts
|

The rising burden of invasive fungal infections in COVID-19, can structured CT thorax change the game

Abstract: Background The occurrence of invasive fungal infections in COVID-19 patients is on surge in countries like India. Several reports related to rhino-nasal-sinus mucormycosis in COVID patients have been published in recent times; however, very less has been reported about invasive pulmonary fungal infections caused mainly by mucor, aspergillus or invasive candida species. We aimed to present 6 sputum culture proved cases of invasive pulmonary fungal infection (four mucormycosis and two invasive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
13
0
4
Order By: Relevance
“…Fungal infection such as aspergillus organism was found in 5 (7.8%) patients and mucor species was found in 50 (78.1%) patients, so mucor species was more common in occurrence than aspergillus organism and bacterial infection. Moreover, Dubey et al, (Dubey et al, 2022) reported a series of 6 covid-19 patients who developed invasive pulmonary fungal infection. They reported that four of them were mucor and remaining two were of candida species.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infection such as aspergillus organism was found in 5 (7.8%) patients and mucor species was found in 50 (78.1%) patients, so mucor species was more common in occurrence than aspergillus organism and bacterial infection. Moreover, Dubey et al, (Dubey et al, 2022) reported a series of 6 covid-19 patients who developed invasive pulmonary fungal infection. They reported that four of them were mucor and remaining two were of candida species.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, it was found that high-resolution computed tomography (HRCT) of the thorax helps in the early detection of these dreadful conditions, following the protocol for patients with chest pain and breathing problems during this pandemic. With the use of HRCT, the cases of the patients were studied, and the following data could be obtained (Dubey 2022 ).…”
Section: Antifungal Treatmentmentioning
confidence: 99%
“…Diabetes patients frequently have morbidity and mortality, and steroid therapy is used to treat COVID-19, which is the main cause for concern (Dubey 2022 ). One strategy to deal with fungal diseases is to monitor the individuals who have the infection, practice good hygiene, watch for the fungus to develop drug resistance, and research and identify the pathology and clinical manifestations of the diseases (Ravikant 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus spreads to CNS with a hematogenous spread directly or as a primary intracranial lesion [141]. Notably, fungal infections are increasing at an alarming rate because of the growing number of immunocompromised patients, the widespread use of immunosuppressive drugs, and the spread of infectious diseases such as AIDS and COVID-19 [142,143]. These fungal infections are secondary to other infections elsewhere in the body and spread to the brain through blood circulation [142].…”
Section: Other Infectionsmentioning
confidence: 99%